The opportunity for partner industry knowledge sharing within audit offices and audit quality - Michas, Paul N.; Russomanno, Dan; Zhao, Meiling (Review of Accounting Studies, 2025)
We conjecture that a greater opportunity for audit partners to share personal industry knowledge with each other within audit offices is associated with higher audit quality. Using Public Company Accounting Oversight Board (PCAOB) Form AP data, we analyze each partner’s client portfolio and construct sharing measures. First, we find extant measures of an audit office’s industry market share, industry portfolio share, and industry diversity are quite noisy in inferring our sharing measures. Next, we perform multivariate analyses and find negative associations between the opportunity to share industry knowledge and both restatements and absolute abnormal accruals. Further, we find this association varies cross-sectionally with other important auditor and client characteristics. Taken together, our evidence is consistent with a positive association between the opportunity for partners to share their industry knowledge with each other and audit quality.